2018
DOI: 10.21037/tgh.2018.07.04
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic distal pancreatectomy: better than open?

Abstract: Distal pancreatectomy is well suited to the laparoscopic approach. Laparoscopic distal pancreatectomy (LDP) provides the same postoperative recovery advantages reputed to minimal access surgery. However, there have been fears as to the safety of LDP in terms of life-threatening intra-operative events and post-operative complications, adequate carcinological outcomes as compared to traditional (open) distal pancreatectomy (ODP) when performed for cancer, as well as to whether the laparoscopic approach is well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 79 publications
1
10
0
1
Order By: Relevance
“…For PDAC that is located in the pancreatic body and tail, minimally invasive DPS is now accepted as the standard of care [59]. A number of factors have contributed to the surgical community adopting this practice.…”
Section: Distal Pancreatectomy and Splenectomy (Dps)mentioning
confidence: 99%
“…For PDAC that is located in the pancreatic body and tail, minimally invasive DPS is now accepted as the standard of care [59]. A number of factors have contributed to the surgical community adopting this practice.…”
Section: Distal Pancreatectomy and Splenectomy (Dps)mentioning
confidence: 99%
“…Multiple studies demonstrate no significant difference in the incidence of postoperative pancreatic fistula formation between PD and DP procedures or between open and laparoscopic DP procedures. 21,22 Despite the less morbid or less extensive DP surgery compared with PD, some other studies have observed that DP has a higher rate of some complications, especially the pancreatic fistula (PF), abscess, and pseudocysts, which are the most common complications of DP. 23 These are described in detail next.…”
Section: Surgical Overview and Expected Postsurgical Appearancesmentioning
confidence: 99%
“…For benign and malignant tumors of pancreas, the laparoscopic technique was adopted relatively late. There is evidence for advantages of the laparoscopic approach in left pancreatectomies compared to open technique [1][2][3][4][5]. Even though many years have passed since the first laparoscopic pancreaticoduodenectomy (LPD) was done, those operations are relatively rarely performed, usually by experienced surgeons in high-volume centers.…”
Section: Introductionmentioning
confidence: 99%